2017
DOI: 10.1002/ijc.30581
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment direct bilirubin and total cholesterol are significant predictors of overall survival in advanced non‐small‐cell lung cancer patients with EGFR mutations

Abstract: This study was designed to examine the prediction of pretreatment circulating bilirubin and cholesterol for overall survival in 459 advanced non-small-cell lung cancer (NSCLC) patients with epidermal growth factor receptor (EGFR) mutations. Circulating total bilirubin, direct bilirubin (DB), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C) levels were measured at baseline. The mean age (standard deviation) of all study patients was 58.7 (10.5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…Although Li et al found that elevated DBIL levels were associated with longer OS in NSCLC, pretreatment DBIL level was not an independent predictor [ 12 ]. Finally, Zhang et al reported that pretreatment DBIL was positively correlated with OS in NSCLC patients with EGFR mutations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Li et al found that elevated DBIL levels were associated with longer OS in NSCLC, pretreatment DBIL level was not an independent predictor [ 12 ]. Finally, Zhang et al reported that pretreatment DBIL was positively correlated with OS in NSCLC patients with EGFR mutations [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is implied that liver functional reserve became poorer with the decrease of TC (Vere et al, 2012; Wang et al, 2014). Several studies have shown low serum TC level and low serum HDL level were associated with worse disease-free survival and overall survival in HCC patients undergoing surgical hepatectomy, breast cancer patients, colorectal cancer patients receiving adjuvant chemotherapy, and non-small-cell lung patients with EGFR mutations (Lee et al, 2016; Li et al, 2016; Wang et al, 2016; Zhang et al, 2017). However, these studies focused on the prognostic significance of single index of TC or HDL in post-surgery patients with cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that lower serum total cholesterol (TC) level correlated with cancer recurrence in HCC patients with hepatic resection, revealing the possibility to predict surgical outcome by preoperative clinical physiological parameters. Poorer surgical outcome in HCC patients with lower preoperative serum TC level might be caused by long-term liver dysfunction and malnutrition, implying the potential role of lipid composition in determination of operative outcomes in HCC patients (Irshad et al, 2007; Wang et al, 2014; Lee et al, 2016; Zhang et al, 2017). Recent studies have reported that serum high-density lipoprotein (HDL) is in relation to incident cancers especially breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…23,26,48 Total cellular cholesterol was shown to be upregulated in gefitinib resistant cells. 23,26,48 Total cellular cholesterol was shown to be upregulated in gefitinib resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of cholesterol synthesis in cancer has been shown to correlate with poor prognosis in patients and plays a role in the development of drug resistance, as overexpression of cholesterol pathway genes has been observed in refractory tumors. 23,26,48 Total cellular cholesterol was shown to be upregulated in gefitinib resistant cells. 20 In this study, cell lines with different sensitivities to gefitinib were used as a model of resistance.…”
Section: Discussionmentioning
confidence: 99%